Cultural history of early South Asia: a reader - Kaul, Shonaleeka (Orient Blackswan, 2014)
Contributed articles; previously published
Contributed articles; previously published. - Includes bibliographical references
Keywords: South Asia -- Civilization; Aufsatzsammlung; Vor- und Frühgeschichte; Kultur; Südasien